Well-defined self-assembling supramolecular structures in water containing a small amount of C60 - Hao, Jingcheng; Li, Hongguang; Liu, Weimin; Hirsch, Andreas (Chemical Communications, 2004)
In this communication, we report for the first time on the spherical bilayer vesicle formation of a dendritic C-amphiphile-surfactant hybrid in aqueous solutions.